Analysis of the Implementation of English Literature Teaching in Middle Schools: Challenges and Potential - Djoleba, Clarisa Zabrina; A'yun, Navisatun Kurrota; Rohmana, Wahyu Indah Mala (Universitas Nahdlatul Ulama Pasuruan, 2023)
English literature teaching plays a crucial role in developing students’ critical thinking, analytical skills, and appreciation for language and culture. However, effectively teaching literature can be challenging due to the complexity of literary texts and the diversity of student learning styles. To address these challenges, teachers need to employ a range of effective teaching strategies that engage students, foster deeper understanding, and stimulate their intellectual growth. By incorporating effective teaching strategies and considerations, English literature teachers can foster a love of literature, critical thinking skills, and intellectual growth in their students, making literature a meaningful and engaging part of their academic journey.